Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Cách 1 : (3/4 + 1/2) x 5/7
= 5/4 x 5/7
= 25/28
Cách 2 : (3/4 + 1/2) x 5/7
= 3/4 x 5/7 + 1/2 x 5/7
= 15/28 + 5/14
= 25/28
b) Cách 1 : 5/7 x 13/21 + 2/7 x 13/21
= 65/147 + 26/147
= 13/21
Cách 2 : 5/7 x 13/21 + 2/7 x 13/21
= (5/7 + 2/7) x 13/21
= 1 x 13/21
= 13/21
câu c tự làm
A =\(\frac{2}{5}\times\frac{4}{7}+\frac{3}{5}\times\frac{4}{7}\) B = \(\frac{17}{13}\times\frac{12}{17}-\frac{4}{13}\times\frac{12}{17}\) C = \(\frac{9}{14}:\frac{6}{7}+\frac{5}{14}:\frac{6}{7}\) D =\(\frac{9}{12}:\frac{7}{9}\times\frac{12}{19}\)
= \(\frac{4}{7}\times\left(\frac{2}{5}+\frac{3}{5}\right)\) =\(\left(\frac{17}{13}-\frac{4}{13}\right)\times\frac{12}{17}\) = \((\frac{9}{14}+\frac{5}{14}):\frac{6}{7}\) = \(\frac{9}{12}\times\frac{9}{7}\times\frac{12}{19}\)
=\(\frac{4}{7}\times1\) = \(1\times\frac{12}{17}\) = \(1:\frac{6}{7}\) = \(\frac{9\times9\times12}{12\times7\times19}\)
=\(\frac{4}{7}\) = \(\frac{12}{17}\) =\(\frac{7}{6}\) = \(\frac{9\times9}{7\times19}=\frac{81}{133}\)
`a: =(7/3-4/3)+11/5=16/5`
`b: =(18/13-5/13)+55/46=1+55/46=101/46`
`c: =27/25-4/9-2/25+5/9=(27/25-2/25)+(5/9-4/9)=1+1/9=10/9`
BÀI 1:
a) \(\frac{4}{5}+\frac{3}{8}+\frac{1}{4}\)
\(=\frac{32}{40}+\frac{15}{40}+\frac{10}{40}\)
\(=\frac{32+15+10}{40}\)\(=\frac{57}{40}\)
b) \(\frac{5}{9}+\frac{2}{3}+\frac{1}{2}\)
\(=\frac{10}{18}+\frac{12}{18}+\frac{9}{18}\)
\(=\frac{10+12+9}{18}=\frac{31}{18}\)
a) \(\left(\frac{1}{5}+\frac{3}{5}\right)\times\frac{1}{4}\)
\(=\frac{4}{5}\times\frac{1}{4}\)
\(=\frac{4}{20}=\frac{1}{5}\)
\(\left(\frac{1}{5}+\frac{3}{5}\right)\times\frac{1}{4}=\frac{1}{5}\times\frac{1}{4}+\frac{3}{5}\times\frac{1}{4}\)
\(=\frac{1}{20}+\frac{3}{20}\)
\(=\frac{4}{20}=\frac{1}{5}\)
b) \(\left(\frac{7}{9}-\frac{2}{9}\right)\times\frac{3}{2}\)
\(=\frac{5}{9}\times\frac{3}{2}\)
\(=\frac{15}{18}=\frac{5}{6}\)
\(\left(\frac{7}{9}-\frac{2}{9}\right)\times\frac{3}{2}=\frac{7}{9}\times\frac{3}{2}-\frac{2}{9}\times\frac{3}{2}\)
\(=\frac{21}{18}-\frac{6}{18}\)
\(=\frac{15}{18}=\frac{5}{6}\)
c) \(\left(\frac{11}{13}-\frac{9}{13}\right)\times\frac{39}{21}\)
\(=\frac{2}{13}\times\frac{39}{21}\)
\(=\frac{78}{273}=\frac{2}{7}\)
\(\left(\frac{11}{13}-\frac{9}{13}\right)\times\frac{39}{21}=\frac{11}{13}\times\frac{39}{21}-\frac{9}{13}\times\frac{39}{21}\)
\(=\frac{429}{273}-\frac{351}{273}\)
\(=\frac{78}{273}=\frac{2}{7}\)
a,\(\left(\frac{1}{5}+\frac{3}{5}\right)x\frac{1}{4}\)
=\(\frac{4}{5}x\frac{1}{4}\)
=\(\frac{4}{20}\)
=\(\frac{1}{5}\)
,\(\left(\frac{1}{5}+\frac{3}{5}\right)x\frac{1}{4}\)
=\(\frac{4}{5}x\frac{1}{4}\)
=\(\frac{4x1}{5x4}\)
=\(\frac{1x1}{5x1}\)
=\(\frac{1}{5}\)